Centrality of Body and Embodiment in Nursing Care: A Scoping Study of the Italian Literature. Issue 1 (18th November 2015) - Marchetti, Anna; Piredda, Michela; De Marinis, Maria Grazia
Abstract: Purpose: Nursing has based its practical work on contact and a relationship with the patient's body and embodiment; however, the international theoretical and empirical researches on these concepts are still neglected. The purpose of this scoping study is to map the breadth and depth with which body and embodiment are addressed in the Italian nursing literature, identifying the key concepts and the main sources and types of evidence available. Organizing Construct: Scoping study with qualitative content analysis. It was conducted in accordance with the framework outlined by Arksey and O'Malley and following the recommendations by Levac, Colquhoun, and O'Brien. The qualitative content analysis process was conducted according to Elo and Kyngäs. Lincoln and Guba's technique was followed to ensure trustworthiness. Methods: Searches were conducted within seven electronic databases of peer‐reviewed literature, one electronic Italian database, six electronic database searches of grey literature, four free online nursing journals, four Internet search engines, and 10 key hard‐copy Italian nursing journals. Findings: Through these searches, 2, 536 records were identified, from which 18 were selected for the final review. Three generic categories emerged from qualitative content analysis: the conceptual category, the nursing care category, and the education category, each including eight, seven, and two subcategories, respectively. Conclusions: The central nursing concepts of body and embodiment definitely require greater and more continuous efforts of theoretical study and empirical research within the nursing discipline, both in Italy and internationally. Clinical Relevance: A greater awareness of body and embodiment should guide nursing practice in caring for and supporting patients and also guide approaches to teaching and learning. Moreover, body and embodiment are concepts firmly rooted in nursing practice, and they are also ripe for future research and able to generate more holistic and complex ways of understanding patients.